Appraisal of antimicrobial properties of Onosma bracteatum Wall. fruit extracts against respiratory tract pathogens - Navneet, Sanjay Kumar, Shiv Shanker Gautam (Journal of Medicinal Herbs and Ethnomedicine, 2015)
The fruit extracts of Onosma bracteatum was extracted with petroleum ether, acetone, methanol, and aqueous solvents and screened for their antimicrobial activity against five bacteria and one fungus causing respiratory tract infections. All extracts showed inhibitory activity against selected pathogens. The crude extracts showed varying levels of bactericidal activity. The methanol extract showed maximum activity ranged between 12.6 Â± 0.28 and 20.6 Â± 0.28 mm at 200 mg/ml. The antifungal activity noted highest with 24.74% inhibition by methanol extract at 250 mg/ml. O. bracteatum can be a suitable source for new antibacterial drug development to cure respiratory diseases.